Building a resilient organic hemp industry: Survey and focus groups assess research, extension, and education needs - Virginia Moore; Emily Fratz; David Baltensperger; Shelby Ellison; Heather Grab; Lynn Sosnoskie; David Suchoff; Daniela Vergara (Agrosystems, Geosciences & Environment)
Abstract Hemp (Cannabis sativa L.) has many potential uses, including in textiles, construction, human food, animal feed, health, and personal care applications, and was once widely grown in the United States. Despite the tremendous initial excitement in hemp production and expansion of hemp acreage following its legalization in 2018, there remains uncertainty and risk surrounding the crop; major gaps in production and processing knowledge and supply and distribution chains exist because of previous legal barriers. In 2023, a national survey of current and prospective organic hemp growers (n = 140) was conducted to identify major challenges associated with organic hemp production and determine what resources and information are needed to support growth and resilience within the industry. A series of focus groups were also conducted with organic hemp growers, hemp educators, and industry stakeholders, including researchers and extensionists, current and prospective hemp business owners, hemp advocates and organizations, and hemp consultants (n = 39). Survey respondents and focus group participants included farmers across a wide range of farm types and sizes, geographic areas, production practices, and end‐use products. Most current hemp producers surveyed are growing hemp for cannabinoid products. Across the survey and focus groups, and regardless of farm type or end‐use product, the most significant challenges of organic hemp production are related to marketing, sales, and regulations. Despite these barriers, most survey respondents are interested in growing hemp in the future; this includes expanded interest in non‐cannabinoid end‐use products such as fiber, grain, seed, or transplants.